Numerical analysis of the flexible manhole-soil interaction in mining areas based on the laboratory test results - Janoszek, Tomasz; Kalisz, Piotr; Zięba, Magdalena (Wroclaw University of Technology, 2024)
Horizontal soil strains, caused by underground mining, change the distribution and values of loads acting on a manhole. The result of a significantly unbalanced distribution of horizontal loads on a flexible manhole is the cross-sectional deflection, which causes passive soil pressure. These loads may damage manholes, leading to failures of the sewer system. The article employs numerical modelling to analyse the interaction between a flexible manhole and horizontally strained soil for the conditions of the performed laboratory tests. The numerical simulations were conducted with FLAC3D v.5.0. software, based on the finite difference method. The numerical analyses showed that in mining areas the cross- -sectional deflection of flexible manhole risers depends on the horizontal soil strains, the ring stiffness of the risers and the foundation depths of manholes.
Mining Science, Vol. 31, 2024, s. 183-198
Keywords: mining; geology; geo-engineering